Exploring Public Recognition and Perceived Cultural Value of the Special Qualities within English Areas of Outstanding Natural Beauty - Isabelle King (MDPI AG, 2021)
As both the concept of ‘landscape’ and ‘beauty’ have very perceptual definitions, they must be assessed by large groups to be appropriately addressed. Therefore, amid a review of AONB designation, cultural perceptions of what is valuable within these designated areas is of paramount importance. Ecosystem services have gained traction as a way to assign social value to the non-physical benefits landscape can provide. AONB landscapes have a list of ‘special qualities’ (SQs) which are the features and characteristics of this area that warrant its protection. This study looks at the extent to which SQs reflect public values. Multiple methods including photo elicitation, participatory mapping, in-person surveys and social media data analysis have been used. The study suggests that when presented with the same landscape there is huge diversity as to what should be considered ‘special’. There is a general preference of landscape heterogeneity, therefore no one SQ could be more important than any of the others if considered in isolation. SQs that have a tangible link to the cultural ecosystem services they provide, were most appreciated. All methods used had their own benefits and flaws, hence future research should use a combination of methods to address perception issues.